GÉANT Plans towards Fibre Infrastructure for the Distribution of Time and Frequency throughout Europe - Vojtech, Josef; Roberts, Guy; Novak, Tomas; Spacek, Michal; Andriantsarazo, Elisabeth; Smotlacha, Vladimir; Havlis, Ondrej; Horvath, Tomas; Vohnout, Rudolf; Slapak, Martin; Roztocil, Jaroslav; Nägele-Jackson, Susanne; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
GÉANT Association aims to establish a fibre infrastructure for the distribution of time and frequency throughout Europe, with the implementation planned within the Horizon Europe GN5-2 funding cycle. These new fibre links will complement existing connections performing predominantly coherent optical frequency transfers, forming a basis of comprehensive Europe-wide infrastructure. This presentation will explore how this emerging fibre network will facilitate novel scientific research initiatives in Europe. Moreover, the development of a pan-European fibre infrastructure will unlock opportunities for pioneering research in applied and fundamental science. This encompasses studies such as geodesy e.g. for underground water monitoring or unification of height systems across Europe, earthquake monitoring, the search for dark matter, and urban activity surveillance.
CRIS-Team Scopus Importer:2024-12-13
Keywords: accurate time; bidirectional transfer; coherent optical frequency; fibre infrastructure; optical fibre; QKD